2021
DOI: 10.1097/apo.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between an Intraocular Lens With Extended Depth of Focus (Tecnis Symfony ZXR00) and a New Monofocal Intraocular Lens With Enhanced Intermediate Vision (Tecnis Eyhance ICB00)

Abstract: Purpose: This study compared the extended depth of focus (EDOF) intraocular lens (IOL) (ZXR00; Tecnis Symfony, Johnson & Johnson Vision, Santa Ana, CA, US) to a novel, higher-order aspheric monofocal IOL (ICB00; Tecnis Eyhance, Johnson & Johnson Vision, Santa Ana, CA, US) which uses the same platform and material. Methods: Medical records of patients undergoing cataract surgery with ZXR00 or ICB00 implantation between March 2020 and January 2021 and with the data available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 50 publications
4
50
2
1
Order By: Relevance
“…A previous clinical study demonstrated that these results were consistent with the results of the present study. Earlier studies have reported monocular UDVAs of 0.13 ± 0.13 6 for ZXR00 and 0.04 ± 0.10 12,30 for ZFR00. Earlier studies have reported monocular CDVA of 0.05 ± 0.08 6 and 0.01 ± 0.02 25 for ZXR00 and −0.02 ± 0.07 12 and −0.04 ± 0.02 25 for ZFR00.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A previous clinical study demonstrated that these results were consistent with the results of the present study. Earlier studies have reported monocular UDVAs of 0.13 ± 0.13 6 for ZXR00 and 0.04 ± 0.10 12,30 for ZFR00. Earlier studies have reported monocular CDVA of 0.05 ± 0.08 6 and 0.01 ± 0.02 25 for ZXR00 and −0.02 ± 0.07 12 and −0.04 ± 0.02 25 for ZFR00.…”
Section: Discussionmentioning
confidence: 81%
“…Earlier studies have reported monocular UDVAs of 0.13 ± 0.13 6 for ZXR00 and 0.04 ± 0.10 12,30 for ZFR00. Earlier studies have reported monocular CDVA of 0.05 ± 0.08 6 and 0.01 ± 0.02 25 for ZXR00 and −0.02 ± 0.07 12 and −0.04 ± 0.02 25 for ZFR00. Likewise, within our study, the UDVA values were 0.08 ± 0.06 and 0.04 ± 0.07 and the CDVA values were 0.01 ± 0.03 and 0.02 ± 0.04 in ZXR00 and ZFR00 groups, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, relatively good UIVA and DCIVA were obtained with both IOLs. Previous studies have compared the Tecnis Eyhance IOL with other EDoF IOLs, such as Tecnis Symphony, a diffractive EDoF IOL 1113 ; however, no study has evaluated the AcrySof IQ Vivity IOL to other EDoF IOLs. Lee et al 11 and Jeon et al 12 reported comparable monocular and binocular DCIVA with Tecnis Symphony and Tecnis Eyhance IOLs, respectively, whereas Corbelli et al 13 reported better monocular and binocular DCIVA with Tecnis Symphony.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the interest of Manuel Rodriguez-Vallejo in our paper, 1 and the comments made to it. There seem to be 2 main points regarding the article.…”
mentioning
confidence: 93%